CHARACTER EDUCATION IN FAMILY THROUGH PARENTING PATTERN - Taat Wulandari; Agustina Tri Wijayanti; Saliman Saliman (Universitas Negeri Yogyakarta, 2019)
This study was aimed at revealing the role and the capital of parenting towards children in an effort to shape the character of tolerance and caring for the environment. The study used qualitative naturalistic research methods. The techniques of collecting data used were observation, interviews, and documentation. The data then analyzed using interactive analysis proposed by Miles and Huberman. The results show that the role of parents in shaping the character of tolerance and caring for the environment through parents as motivators, as supervisors, as physical and spiritual protectors, as mentors, educating and as role models or role models to choose and shape children. The formation of the character of tolerance and caring for the children is given through debriefing skills to respect friends, stimulation activities, and positive habituation application. The pattern of positive habituation of parents is in the form of familiarizing children to do good activities. Parents provide firmness to the child's character of tolerance and caring for the environment. The model of parenting is applied as authoritarian parenting, democratic and situational.PENDIDIKAN KARAKTER DALAM KELUARGA MELALUI POLA ASUH ORANG TUAPenelitian ini bertujuan untuk mengungkapkan peran dan modal pola asuh orang tua terhadap anak dalam upaya membentuk karakter toleransi dan peduli lingkungan. Penelitian menggunakan metode penelitian kualitatif naturalistik. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan analisis interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa peran orang tua dalam membentuk karakter toleransi dan peduli lingkungan dapat melalui orang tua sebagai motivator, sebagai pengawas, sebagai pelindung jasmani dan rohani, sebagai pembimbing, mendidik dan sebagai panutan atau role model untuk memilihara dan membentuk anak. Pembentukan karakter toleransi dan peduli lingkungan pada anak diberikan melalui pemberin bekal keterampilan untuk saling menghargai dengan sesama teman, orang tua membentuk kegiatan yang merangsang karakter toleransi dan peduli lingkungan, orang tua menerapkan pembiasaan yang positif. Pola pembiasaan positif orang tua dilakukan dengan membiasakan anak melakukan kegiatan yang baik. Orang tua memberikan ketegasan terhadap anak karakter toleransi dan peduli lingkungan. Model pola asuh orang tua yang diterapkan seperti pola asuh otoriter; demokratis dan situasional.